DENTAL ANOMALIES AND ORAL HYGIENE STATUS IN MENTALLY RETARDED CHILDREN - B, ABIJETH; KUMAR, SARAVANA; K, DURGHA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
OBJECTIVE: Mental retardation is a condition in which there isÂ deficiency in all development of motor, cognitive, social, emotional, chronic medical conditions Â and language functions.Â This is the commonest form of developmental disability.Â It is related to Â nervous system function. Many people with mental retardation also suffer from other disabilities such as cerebral palsy, seizure or psychiatric disorders, attention disorders, hyperactivity, visual abnormalities , communication inability and difficulty in mastication and deglutation. Oral hygiene of these mentally compromised children are not the same as it is found in normal healthy individual. The mentally challenged children maintain a poor oral hygiene and thus they are prone to various oral diseases and anomalies which requires diagnosis and treatment.Adequate oral cleaning in these mentally compromised children is a difficult task due to their improper musculature. They have a high risk of incidence of periodontal disease, malocclusion, drooling of saliva, macroglossia, fissured tongue andÂ high arched palate. METHOD: This study was conducted among 67 patients who fall under the age group of 12-20 years. RESULTS: The clinical findings were significant including higher prevalence of malocclusion, fissured tongue,high arched palate, drooling of saliva,angular chelitis, fractured tooth. CONCLUSION: This study was carried out among the mentally challenged children to know their oral hygiene status and dental anomalies with an idea of guidingÂ them to have a good oral hygiene status and treat the developed dental changes.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â KEYWORDS : Mental retardation, Poor Oral Hygiene, Dental Anomalies ,Malocclusion, Â Fissured tongue